A Cognitive Stylistic Analysis of Daily Yahoo Stories - Hassoon, Fatimah Kudhair (Al-Adab Journal, 2019)
Cognitive stylistics is one discipline of applied linguistics that relies on the reader’s interpretation and inference of the meaning of the text depending on his background knowledge. It studies how the reader understands the text and mapping it with his real experiences (Jeffries and McIntyre,2010). The present study is a cognitive stylistic analysis of digital stories. Digital stories are short narratives made by a combination of different sorts of digital media such as pictures, audios and videos. These digital media are employed to tell stories about oneself, famous people, and important events. The analyzed stories are selected from “Daily Yahoo Stories” and are analyzed according to Lakoff (1993) approach, The analysis investigates the use of figures of speech in this type of stories and how they are mapped with the reader’s perceptions. The results show that figures of speech like simile, personification and metaphor do exist in everyday language. Also the use of multimedia alongside with the use of figures of speech in digital stories play a great role in interpreting and understanding the text by the reader